COVID‐19 and coworker conflict among emergency medical service clinicians - Gennaro Di Tosto; Halia Melnyk; Jonathan R. Powell; Eben Kenah; Christopher B. Gage; Ashish R. Panchal; Ann Scheck McAlearney (Journal of the American College of Emergency Physicians Open)
Abstract Objectives Safety policies enacted in response to the emergence of coronavirus disease 2019 (COVID‐19) have greatly affected the working environments of emergency medical service (EMS) clinicians. Our objective was to evaluate whether changes in the EMS environment during the COVID‐19 pandemic were associated with increased workplace conflict. Methods This evaluation was a cross‐sectional analysis of a random sample of 19,497 national certified EMS clinicians who were selected to receive an electronic survey in April 2022. The survey included an assessment of their level of stress using the Perceived Stress Scale instrument and examined changes in their working environment they perceived had occurred due to the emergence of COVID‐19. Logistic regression modeling was used to evaluate the associations between workforce demographics, infrastructure, scheduling, and policies to and COVID‐19‐induced coworker conflict. Results A total of 1686 responses were evaluated (response rate 10%). We found that COVID‐19 was reported to have exacerbated conflict between coworkers in 51% of responses. Respondents who perceived an increase in coworker conflict due to COVID‐19 self‐reported higher levels of stress than the rest of the respondents. Perceptions of the impact of COVID‐19 on conflict had also an association with the level of certification, indicating that national registered paramedics were more likely than emergency medical technicians to report coworker conflict due to COVID‐19 (adjusted odds ratio [AOR] 1.30, 95% confidence interval [CI] 1.05–1.61). Multivariable analysis highlighted the impact of mandatory overtime policies, reported by 27% of the respondents and associated with higher odds of exacerbated coworker conflict in our model (AOR 2.05, 95% CI 1.62–2.60). Conclusions These findings indicate that conflict can be considered a potential indicator of high levels of stress in the EMS workforce and may be a reliable signal to monitor when implementing mandates that affect EMS clinicians and their workloads.